Chavista 'thugs' vs. opposition 'civil society': western media on Venezuela. (April 2019) - MacLeod, Alan
Since the election of Hugo Chavez in 1998, Venezuela has undergone a period of intense racial and class conflict, as a multiethnic subaltern coalition has begun to assert itself politically against a previously hegemonic and inordinately dominant white elite. Scholars have highlighted the local media's racial and class snobbery when covering social movements and civil society, attempting to split the country into two groups: 'underclass mobs' and 'respectable' civil society. This article, which analyses media coverage at crucial points of conflict – 1998/9, 2002, 2013 and 2014 – finds that western media have overwhelmingly matched the local media, portraying only the largely dark-skinned working-class chavista groups as vicious 'mobs', 'hordes' and 'thugs', while representing the white, upper-class opposition as 'civil society'.